A cortical–subcortical syntax pathway linking Broca's area and the striatum. Issue 6 (16th February 2015) - Teichmann, Marc; Rosso, Charlotte; Martini, Jean‐Baptiste; Bloch, Isabelle; Brugières, Pierre; Duffau, Hugues; Lehéricy, Stéphane; Bachoud‐Lévi, Anne‐Catherine
Abstract Combinatorial syntax has been shown to be underpinned by cortical key regions such as Broca's area and temporal cortices, and by subcortical structures such as the striatum. The cortical regions are connected via several cortico‐to‐cortical tracts impacting syntactic processing (e.g., the arcuate) but it remains unclear whether and how the striatum can be integrated into this cortex‐centered syntax network. Here, we used a systematic stepwise approach to investigate the existence and syntactic function of an additional deep Broca‐striatum pathway. We first asked 15 healthy controls and 12 patients with frontal/striatal lesions to perform three syntax tests. The results obtained were subjected to voxel‐based lesion‐symptom mapping (VLSM) to provide an anatomo‐functional approximation of the pathway. The significant VLSM clusters were then overlapped with the probability maps of four cortico‐cortical language tracts generated for 12 healthy participants (arcuate, extreme capsule fiber system, uncinate, aslant), including a probabilistic Broca‐striatum tract. Finally, we carried out quantitative analyses of the relationship between the lesion load along the tracts and syntactic processing, by calculating tract‐lesion overlap for each patient and analyzing the correlation with syntactic data. Our findings revealed a Broca‐striatum tract linking BA45 with the left caudate head and overlapping with VLSM voxel clusters relating to complex syntax. The lesion load values for this tract were correlated with complex syntax scores, whereas no such correlation was observed for the other tracts. These results extend current syntax‐network models, by adding a deep "Broca‐caudate pathway, " and are consistent with functional accounts of frontostriatal circuits. Hum Brain Mapp 36:2270–2283, 2015. © 2015 Wiley Periodicals, Inc.